KEPEMIMPINAN PENDIDIKAN : KEKUASAAN, POLITIK DAN ETIKA DALAM MENGEMBANGKAN BUDAYA MUTU - Rahman, Kholilur (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2017)
In the Organization of at least need two individuals are related, then it takes one person acting as a leader. Educational leaders in carrying out tasks and implement its vision and mission in need of power (power). By having the power, the leader obtains an instrument to affect the behavior of followers. Leaders should not just assess his conduct themselves so that they can understand how they affect the behavior of other people, but also a leader should be willing and able to assess their positions and how to use the power. Power as part of the inhern leadership is closely linked with ethics. In the implementation of power and leadership are certainly going the process of communication and interaction between multiple people within an organization. In the process, the leader will use the power in all its aspects. Leaders can use their powers for good or evil, as well as the values and code of ethics. A leader may be the one deciding factor of how these leaders use a variety of power sources that are available to bring the institution with quality services.